Mitigating Urban Heating in Dryland Cities: A Literature Review. (November 2019) - Wheeler, Stephen M.; Abunnasr, Yaser; Dialesandro, John; Assaf, Eleni; Agopian, Sarine; Gamberini, Virginia Carter
This review analyzes literature regarding urban heating and urban heat islands (UHIs) in dryland cities. This topic is of widespread importance in the era of climate change since many global cities are in arid, semiarid, or Mediterranean regions. We first analyze the literature on dryland UHIs, finding major differences with those for temperate cities. We then review research on cooling strategies involving vegetation, built form, and materials. Finally, we consider planning dimensions. Overall, we find that the most sustainable cooling approach for dryland cities is likely to combine low-water tree species with dense, shade-producing built form and high-albedo materials.